Pengembangan Media Video Pembelajaran Pemasangan Panel Hubung Bagi Tiga Fase di Program Studi S1 Pendidikan Teknik Elektro Undiksha - Putu Eva Aristana Aristana; Agus Adiarta; I Putu Suka Arsa (Universitas Pendidikan Ganesha, 2022)
This study aims to create a video learning for the installation of a three-connection panel to phase determine the feasibility and responses of students to the media for the video instructional installation of a three-phase connection PHB in the electrical engineering education undergraduate course. This research uses research and development methods Research and Development (R&D). Data collection in this study was carried out using a questionnaire/questionnaire method which was assessed by content experts, media experts, and students in the Electrical Engineering Education study program. The validation results from content experts get a percentage score of 96.15% very feasible qualification, media expert validation test results get a percentage score of 96.42% very decent qualifications, small group test scores get a percentage score of 100% with very good qualifications, and the results of the large group test scores get a percentage score of 100% with very good qualifications. Based on the results of the research, the media video instructional for the installation of a three-junction panel was phase feasible and received a very good response from students in the junction PHB subject in the Undiksha Electrical Engineering Education study program.